Microstructure and mechanical properties of spark plasma sintered Al2O3-SiC-CNTs hybrid nanocomposites. Issue 10 (1st August 2016) - Saheb, N.; Mohammad, K.
Abstract: The ever-increasing demand for high-performance ceramic-based materials is difficult to meet with conventional ceramic composites because of their limited fracture toughness. Hybrid microstructure design, achieved by incorporating two nanoreinforcements with different morphologies, is a new approach that has been adopted to develop ceramic materials with improved fracture toughness. In this work, Al2 O3 -SiC-CNTs hybrid nanocomposites were synthesized by ball milling, sonication, and spark plasma sintering (SPS) at 1500 °C for 10 min. The obtained materials were characterized at all stages, from powder synthesis to sintering, using field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), and X-ray mapping. The influence of SiC nanoparticles and CNTs on the microstructure, densification, hardness, and fracture toughness of the composites was investigated. The uniform distribution of SiC and CNTs obtained by sonication and ball milling was maintained in the consolidated samples. The final microstructure comprised intergranular CNTs, along with inter- and intragranular SiC nanoparticles. Almost fully dense hybrid nanocomposites were obtained (higher than 98%). The addition of SiC to alumina changed its fracture mode from intergranular to a mixture of intergranular and transgranular modes. An almost complete transgranular fracture mode was observed for the hybrid composites, i.e., when CNTs were added to Al2 O3 -SiC nanocomposites. The Al2 O3 -10SiC-2CNTs hybrid nanocomposite possessed the highest fracture toughness, an increase of 93.95% compared to alumina. The Al2 O3 -10SiC-1CNTs hybrid nanocomposite possessed the highest hardness, an increase of 12.12% compared to alumina.